2004
DOI: 10.1007/s00134-004-2319-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of oral clonidine for sedation in ventilated paediatric intensive care patients

Abstract: Oral clonidine may be a safe and effective sedative in combination with morphine and lorazepam for young children with single-organ, respiratory failure. This agent may also exhibit opioid and benzodiazepine sparing effects in this patient group. A full pharmacokinetic study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 20 publications
3
80
0
Order By: Relevance
“…Clonidine, when used in combination with intravenous opioids, reduces total opioid use in infants 42. Thus, clonidine is likely to be effective when combined with oral morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine, when used in combination with intravenous opioids, reduces total opioid use in infants 42. Thus, clonidine is likely to be effective when combined with oral morphine.…”
Section: Discussionmentioning
confidence: 99%
“…For ICU patients in general, appropriate sedation can avert delirium, which has a highly adverse impact on later prognosis [85][86][87][88][89]. Clonidine has been applied in this setting [90][91][92], but dexmedetomidine is currently the only ␣ 2 -agonist approved for use in the ICU in several countries. Dexmedetomidine is distinguished by the quality of sedation it confers [93]: patients sedated with dexmedetomidine are characteristically easy to rouse but lapse into a tranquil, sleep-like state with no respiratory depression [94] when left undisturbed.…”
Section: Sedationmentioning
confidence: 99%
“…Arenas-López et al [18] demonstrated a consistent and adequate level of sedation in the majority of cases at clonidine plasma concentrations of 0.9-2.5 ng/ml. Sumiya et al [19] reported that the plasma clonidine concentration of 0.3-0.8 ng/ml would be sufficient to produce a satisfactory sedation in pediatric surgery.…”
Section: Discussionmentioning
confidence: 99%